Characterization and analysis of the molecular weight of lignin for biorefining studies. (4th June 2014) - Tolbert, Allison; Akinosho, Hannah; Khunsupat, Ratayakorn; Naskar, Amit K.; Ragauskas, Arthur J.
Abstract The molecular weight of lignin is a fundamental property that influences the recalcitrance of biomass and the valorization of lignin. The determination of the molecular weight of lignin in native biomass is dependent on the bioresources used and the isolation and purification procedures employed. The three most commonly employed isolation methods are milled wood lignin (MWL), cellulolytic enzyme lignin (CEL), and enzymatic mild acidolysis lignin (EMAL). Common characterization techniques for determining the molecular weight of lignin will be addressed, with an emphasis on gel permeation chromatography (GPC). This review also examines the mechanisms behind several biological, physical, and chemical pre‐treatments and their impact on the molecular weight of lignin. The number average molecular weight (Mn), weight average molecular weight (Mw) and polydispersity index (D) all vary in magnitude depending on the biomass source, pre‐treatment conditions, and isolation method. Additionally, there is a growing body of literature that supports changes in the molecular weight of lignin in response to genetic modifications in the lignin biosynthetic pathways. This review summarizes different procedures for obtaining the molecular weight of lignin that have been used in recent years and highlight future opportunities for applications of lignin. © 2014 Society of Chemical Industry and John Wiley & Sons, Ltd